Naming the ghost: self-naming, pseudonyms, and identities of phantoms on Zimbabwean twitter - Chibuwe, Albert; Mpofu, Phillip; Bhowa, Kudakwashe (SAGE Publications, 2022)
In Zimbabwean online spaces, especially Twitter, use of phantom names is widespread. It is arguable that this is partially a result of the country’s repressive political environment. It is the names that the nameless Twitter characters select and the motivations for using specific names that are the focus of this present study. The study is grounded in anthroponomastic concepts of pseudonymity and self-naming, and self-presentation and identity theory as well as semiotics of names while methodologically it is qualitative. Specifically, the study deploys archival research and netnography to gather data. The study found out that the ghosts’ adopted names are reflective of what they tweeted. The messages they tweeted were reflective of the online identity that they assumed; however, over and beyond that, their tweets exposed their political, and to an extent, religious inclinations. The tweets also exposed their origins and the spaces they once occupied or currently occupy. Finally, the article concludes that hiding behind a ghost name may hide the name of the person but it certainly does not hide the identity/identities of the person behind the phantom name. His or her being is self-evident in his or her tweets—they imprint themselves into their tweets. The anonymity in online spaces may, after all, be just superficial.